Habermasian Theory and the Development of Critical Theoretical Discourses in Adult Education - Patricia A. Gouthro (Adult Education Research Conference, 2002)
This paper begins with an overview of Habermas’s background, discusses some of his theoretical contributions, explores ways his ideas have been interpreted and utilized by adult educators, and briefly notes some of the critiques of his work.